Effect of PEG on Performance of NiMnO Catalyst for Hydrogen Evolution Reaction - Zeng, Jinfeng; Chen, Lu; Li, Linlin; Yang, Wei; Zou, Hanbo; Chen, Shengzhou (Frontiers in Chemistry, 2020)
Solvothermal method is a very common synthetic method in the preparation of catalysts for the hydrogen evolution reaction (HER) of H2O decomposition. Since a certain surfactant can be added to the solvothermal solvent, the crystal particle growth process can be changed to obtain catalysts with different morphologies. We synthesized a series of nickel-manganese oxides (NiMnO) by adding different amounts of Polyethylene glycol (PEG) using the solvothermal method. Structure characterizations exhibit that NiMnO catalyst prepared with different PEG additions have different morphologies. The NiMnO catalyst prepared by adding 3 g of PEG possesses abundant petal-like scales, it brings a large specific surface area, high reaction efficiency, and has the best electrocatalytic activity in alkaline media.